Right-Wing Populism and Macroeconomic Shocks in Germany and Bulgaria - Станков, Петър (Научни трудове, 2018)
I study right-wing populism in Germany and Bulgaria since 1980. The data is a merge between Heino in levels produce that: 1) income per capita growth coincides with right-wing populist insurgence; 2) a rise of unemployment, income inequality, trade openness and net migration correlates with more right-wing populism; 3) the effects are stronger after the Great Recession.
Keywords: Десен популизъм; Германия; България; Рецесия; Миграция; Доходно неравенство